COVID-19 Contingency Planning Among Radiologic Science Programs. - Clark, Kevin R.; Webster, Tammy L. (Radiation Therapist)
Purpose To examine radiologic science programs' contingency planning related to the COVID-19 pandemic. Methods Using a mixed-methods approach, educators in magnetic resonance, medical dosimetry, radiation therapy, and radiography programs were surveyed to identify curricular changes, policy implementation, and financial implications related to pandemic recovery efforts. Quantitative data were summarized using descriptive statistics and percentages. Thematic analyses were performed on the qualitative responses. Results Continued curricular changes involved using technology to teach in the online environment and ensuring the safety and protection of students during clinical rotations. Institutional policies implemented because of the pandemic included social distancing guidelines, mask requirements, and availability of vaccine. The greatest financial implication witnessed among the sample of educators at their respective institutions was the halting of employer-related travel. Faced with the spontaneous shift to online learning while not being equipped with the appropriate training, most of the educator participants experienced COVID-19 fatigue and burnout related to teaching online. Discussion Social distancing guidelines make it difficult for large classes to meet in person, so virtual lectures using video conferencing platforms were an essential part of teaching during the pandemic. Most educators in this study selected recording technology for lectures as the most useful educational technology tool integrated into the didactic portion of their program. For many educators, having administration realize the adoption of technology is integral to and viable for radiologic science programs was a positive outcome of COVID-19. The pandemic caused educators in the study to experience fatigue and burnout related to online learning; however, the educators also expressed a high degree of comfort with using technology in the online learning environment. This implies that the source of fatigue and burnout was likely not associated with the technology, but with the focused and swift transition to predominately online learning. Conclusion Although educators in this sample felt moderately prepared to handle future viral outbreaks and extremely comfortable using technology in the virtual classroom, additional research is needed to develop viable contingency plans and explore pedagogical approaches to content delivery beyond the traditional, in-person structure.